VD_FINDINFO MP / 2009 / 2 vom 30. Juni 2009 - VD Tribunal cantonal (2009)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, MESURE PROVISIONNELLE | 837 al. 1 ch. 3 CC, 839 al. 2 CC, 961 al. 3 CC, 102 CO, 104 al. 1 CO